The prevalence and genotypic analysis of Toxoplasma gondii from individuals in Scotland, 2006–2012. Issue 1 (December 2016) - Burrells, Alison; Opsteegh, Marieke; Pollock, Kevin; Alexander, Claire; Chatterton, Jean; Evans, Roger; Walker, Robert; McKenzie, Chris-Anne; Hill, Dolores; Innes, Elisabeth; Katzer, Frank
Abstract Background Contemporary information relating to the prevalence ofToxoplasma gondii in humans is lacking for the UK population, with even less information available about the human prevalence of the parasite in Scotland. To address this, two different study groups were used to determine the prevalence and genotypes ofToxoplasma gondii in the Scottish population. Methods The first study group included serum samples from blood donors (n  = 3273) over a four-year period (2006–2009) and the second study group comprised of DNA samples extracted from human brains (n  = 151) over a five-year period (2008–2012). AT. gondii IgG ELISA was performed to determine seroprevalence and available sera from individuals who had seroconverted were tested by TgERP ELISA (sporozoite specific antigen). Human brain DNA was tested forT. gondii by ITS1 PCR and positives genotyped at the SAG3 and GRA6 loci by PCR-RFLP analysis. Results Seroprevalence toT. gondii from blood donors was found to be 13.2 % (95 % CI: 11.5–15.1 %). Evidence of seroconversion (n  = 2) as well as reversion to sero-negative status (n  = 6) was evident from blood donors who had donated within all four collection periods (n  = 184). The TgERP ELISA (indicating oocyst infection) was positive for one individual. The molecular detection ofT. gondii DNA from human brains indicated a prevalence of 17.9 % (95 % CI: 12.1–24.9 %), with genotyping identifying alleles for types I and III. An increase in age was associated with an increase in detection of the parasite within both study groups. Conclusions Our research provides current figures for the prevalence ofT. gondii in Scotland and also shows evidence of seroreversion within the cohort of blood donors. In both study groups there was a correlation between increasing age and an increase inT. gondii prevalence, indicating that acquired infection plays an important role within the Scottish population.